Nursing consultation to elderly people based on andragogy: a review article - Luccas Melo de Souza; Liana Lautert; Johannes Doll; Maria Cristina Sant'Anna da Silva (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
This is a review article which aims at presenting andragogy as the science that can orients the education of elderly people, in order to provide theoretical construct to grant nursing consultations to those individuals. For this, its concepts are approached and its assumptions are discussed, based in the six premises elaborated by Malcolm Knowles. This article starts from an extended vision of elderly, in which the mission of nurse/educator is to help them to develop their potential, considering their social atmosphere, their personal and collective experiences and their expectations. It is believed that nurses can use the andragogy theory, because it is perceived that it presents elements that can be added to the nursing consultation.